Molecular cloning of a highly leukemogenic, ecotropic retrovirus from an AKR mouse. - Lenz, J (1982)
SL3-3 is a leukemogenic, ecotropic retrovirus produced by a T-cell line derived from a spontaneous lymphoma of an AKR mouse. We have isolated a molecular clone of its DNA provirus from infected NIH 3T3 fibroblasts. Cloned proviral DNA produced infectious virus upon transfection onto NIH 3T3 cells. Virus derived by transfection induced lymphomas at high frequency in AKR/J, C3H(f)/Bi, CBA/J, and NFS/N mice. Heteroduplex and RNase T1 fingerprinting analyses showed that the genomes of SL3-3 and the non-leukemogenic virus, Akv, contain no major substitutions relative to one another and differ by only a few base changes. These results unambiguously show that SL3-3 is a highly leukemogenic virus and that major rearrangements of the genome relative to Akv are not required for virulence.